Observers Have Similar Improvements in Student Learning Outcomes as Participants in Athletic Training Simulation Education: A Pilot Study - Alma Mattocks; Sara Mahoney; Rachele Vogelpohl; Kim Hawkins (Bowling Green State University, 2024)
Introduction: The use of standardized patient (SP) encounters in athletic training education programs have become more common; however, due to time and space constraints, it is possible that not all athletic training students will be able to participate and some must be observers. The objective of this study was to determine if observers experience similar improvements in student learning outcomes as participants for SP encounters. Methods: A pretest/posttest, non-randomized controlled trial was utilized. Nine athletic training students volunteered to participate in the research study. All participants completed a pretest survey including a knowledge assessment and confidence rating scale, followed by either a telehealth or in-person SP encounter of a lower extremity evaluation, and finished with a posttest survey. Results: Two separate repeated measures ANOVAs of the composite knowledge scores and confidence rating scale found significant differences between the pretest and posttest respectively (F = 14.117, p = 0.007, = 0.669; F = 88.439, p < 0.001, = 0.927), with no significant difference between the participant or observer roles for either knowledge assessment (F = 0.213, p = 0.658, = 0.030) or confidence rating scale (F = 2.669, p = 0.146, = 0.276). Conclusion: Athletic training students demonstrated similar increases in knowledge and confidence as a result of telehealth and in-person SP encounters regardless of their role as an observer or participant. Athletic training educators should consider implementing SP encounters into their educational curriculums even if not all students are be able to be participants.